Risk knowledge and concern as influences of purchase intention for internet of things devices. (August 2020) - Aggarwal, Nitin; Albert, Leslie J.; Hill, Timothy R.; Rodan, Simon A.
Abstract: Consumer demand for Internet of Things (IoT) devices is projected to continue its lucrative acceleration despite growing cybersecurity concerns and incidents reported in the public press. We explore this apparent anomaly through a model, based on the relevant literature, casting consumers' IoT Purchase Intention as driven by their pre-existing IoT Risk Knowledge, their level of IoT-related Security Concern, and their device-specific perceptions of Riskiness and Coolness. Based on this model, we collected survey data gauging Purchase Intention for four products varying in Riskiness and Coolness levels. Our analysis extends prior research by confirming the negative influence of IoT Risk Knowledge, implicating it as an emerging drag on IoT consumer demand growth. We further confirm the expected effects of Device Riskiness (negative) and Coolness (positive) as primary factors and we note the cognitive dissonance implied by the inherent IoT device trade-off: greater Coolness tends to come at the price of greater Riskiness. In this trade-off, Coolness mattered more for consumers with lower IoT Security Concern suggesting greater susceptibility to the "wow" factor as offsetting or even distracting from the associated risk. This work contributes to the literature by confirming antecedents and revealing subtleties in the interplay of general and device-specific factors affecting consumer IoT Purchase Intention, shedding light on the feature-attraction/risk-avoidance paradox and identifying implications for both research and practice as the marketplace and consumer perceptions co-evolve going forward. Highlights: Prior IoT Risk Knowledge negatively affects Purchase Intention, growing market drag. Perceived Coolness increases IoT Purchase Intention and Perceived Riskiness dampens it. Perceived Device Riskiness mediates the influence of IoT Risk Knowledge on Purchase Intention. Coolness matters more strongly for consumers with low IoT Security Concern than for those with high IoT Security Concern. For those with low IoT security concern, Purchase Intention increases with Riskiness.